Design and research of power system Beidou timing and positioning module based on K‐means clustering and gross error processing - Yawei Xu; Wei Wang; Xiaona Yang; Ke Deng; Zhiyuan He (IET Cyber-Physical Systems, 2023)
Abstract The clock synchronisation of the power system is to realise the clock synchronisation of the whole network. The clock synchronisation network is composed of the clock synchronisation systems of power grids at all levels. Dispatching agencies, power plants, and substations have their clock synchronisation systems. By using computer technology, communication technology, and network technology, combined with the topological structure of the power grid and geographic information of the geographic information system, automatically process the key index data to ensure that the distribution network project can manage the power consumption and distribution 24 h without interruption. Considering the particularity of power, the accuracy of the receiver is strictly required, and so are the positioning, speed measurement, and time accuracy. Test indicators study a set of accurate and reliable test and evaluation methods. A gross error processing method based on the k‐means algorithm is proposed. Experiments show that gross errors can be well identified and eliminated in one‐dimensional and multidimensional data. Considering that invalid data may be hidden in the test data, to improve the identification accuracy without affecting the detection of normal gross errors, based on the proposed k‐means algorithm, the number of visible satellites is added. Because the magnitude difference between the number of visible satellites and the original three‐dimensional positioning error data is relatively large, it is normalised first. The processing data is extended from three‐dimensional to four‐dimensional. The experimental simulation shows that it can not only identify invalid data but also ensure a good effect of gross error elimination, reduce possible economic losses, bring significant direct and indirect economic benefits, and verify the feasibility and promotional value of the online monitoring platform through practice.